Transmission Electron Microscopic Studies On In Vitro Biofilm Formation By Escherichia Coli From Bovine Mastitis Cases - KAVITHA G; S ISLOOR; D RATHNAMMA; Y B RAJESHWARI; B M VEEREGOWDA; S NAGARAJA (International Journal of Pharma and Bio Sciences, 2011)
When bacteria grow in vivo, they must cope up with a hostile environment in which certain nutrients are not adequate, and where the host attempts to eliminate them in different ways. In such situations, bacteria use certain survival strategies by forming biofilms. In the present study, an in vitro technique was designed to grow Escherichia coli serotype isolated from bovine mastitis cases, in planktonic mode under nutrient rich condition (3% TSB) and also in biofilm mode, by incorporating bentonite clay (0.3%) under nutrient restricted condition (0.16% TSB). Sequential steps involved in the formation of biofilms in vitro by E.coli were studied by TEM. E.coli grown in planktonic mode had the architecture of rod shape with extracellular appendages. Also, the cells grown in biofilm mode were same as that of cells grown in planktonic mode. In the later stages, bacterium was attached to the surface of bentonite clay. Transition from planktonic state to the biofilm state requires a developmental alteration in flagellae, fimbriae or pili i.e. repression of extracellular appendages and expression of exopolysaccharide leading to formation of microcolonies, a 3-D architecture of mature biofilms (Phase variation).